A course in environmental economics theory, policy, and practice - Phaneuf, Daniel J. (Cambridge University Press, 2023)
This graduate textbook draws on the latest international research to present a compelling narrative of environmental economics that integrates theory, policy, and empirical topics. It includes both traditional and emerging perspectives, and provides students with numerous data-based examples and exercises to develop their skills.